Assessment and quantitative analysis of hip surrounding muscles in children with developmental dysplasia of the hip via magnetic resonance imaging - Duan, Lian; Zhou, Weizheng; Li, Lianyong (Journal of orthopaedic surgery and research, 2024)
The muscles that encase the hip serve a crucial role in both joint stability and functional efficacy, and as developmental dysplasia of the hip (DDH) progresses, the surrounding musculature may undergo specific adaptations that reduce joint stability, thereby exacerbating dislocation. Yet, the exact nature of changes in muscle morphology and quality remains inadequately investigated. This study aimed to compare magnetic resonance imaging (MRI) evaluations of the iliopsoas and other hip flexor and extensor muscles in children with unilateral DDH before and after treatment. Children with unilateral DDH were included in this study and compared to a matched control group. Using T2-weighted MRI sequences, muscle cross-sectional area (CSA) and fat infiltration (FI) were measured for the iliopsoas, sartorius, rectus femoris, tensor fasciae latae, and gluteus maximus. The cross-sectional area ratio (CSAr) was calculated as the CSA of the affected side divided by the CSA of the healthy side, corresponding to the respective sides in normal controls. For long-term follow-up (≥ 5 years), data from DDH children were analyzed, categorized into groups based on treatment. Comparisons of muscle CSAr and FI at the final follow-up were made against preoperative levels. Preoperative median CSAr values for the iliopsoas, rectus femoris, and gluteus maximus in DDH children were significantly lower than those of the control group (P < 0.001). FI levels were also higher in the DDH group compared to controls. In the closed reduction group, iliopsoas CSAr increased and FI decreased at the final follow-up compared to preoperative measurements. Conversely, in the open reduction group, iliopsoas CSAr and FI decreased. In the Dega osteotomy group, both iliopsoas CSAr and FI decreased, while CSAr for the sartorius, rectus femoris, and gluteus maximus increased, with also reduced FI. Children with DDH exhibit varying degrees of muscle atrophy and increased fat infiltration compared to their age-matched healthy counterparts. Aside from the iliopsoas, muscle morphology and fat infiltration in DDH children improved post-treatment compared to pre-treatment levels.